Topsy-Turvy Heart: A Very Rare Congenital Rotational Heart Disease With Tracheobronchial Anomalies - AKALIN, FİGEN; ÖZTÜRK, MAKBULE NİLÜFER; ARSAN, SİNAN (My University, 2013)
The topsy-turvy heart is characterized by a global 90°clockwise rotation around the heart’s long axis. This rotation displaces all basal great arteries inferiorly and posteriorly, resulting in elongation and stretching of the brachiocephalic arteries and the bronchi. To date, reports of only four living cases have been published in the literature. We report here three new cases, with additional aortopulmonary window defects, and present their morphological details, clinical presentations, and our management. © 2013, SAGE Publications. All rights reserved.
Keywords: airway; aortic arch; bronchus; cardiac anatomy; congenital heart disease